Analisis Konsep Fisika Kesetimbangan pada Perahu Cadik Bimorejo Banyuwangi - Rif'ati Dina Handayani; Sri Handono Budi Prastowo; Rahmania Amanah Putri (Jurnal Penelitian Pendidikan IPA, 2022)
Indonesia has a lot of local culture in the marine sector, which is starting to disappear due to the impact of globalization, one of which is the Cadik boat located in Bimorejo Village, Banyuwangi. The purpose of this research is to analyze the concept of equilibrium physics on the Cadik boat. This type of research is qualitative research with interview, observation and documentation data collection methods. The data were analyzed using content analysis which consisted of seven stages, including Defining the research question, defining the population and samples, defining the units of analysis, deciding the codes, constructing the categories, conducting the data analysis, and creating inferences. The results showed that there was an equilibrium concept on the Cadik boat. The body of the boat and the outrigger provide equal and opposite forces to fulfil the equilibrium requirements Î£F= 0 and the outriggers on the sides of the boat have the same mass and length, thus fulfilling the equilibrium requirements Î£Ï„ = 0. This research is expected to provide a new perspective for teachers and students so that physics learning is more contextual and meaningful.